Analisis Implementasi Projek Lintas Mata Pelajaran melalui Program P5 dalam Membangun Karakter di Madrasah Aliyah - Tri Kurniawati; Desnita Desnita; Fauzan Aulia (Jurnal Ecogen, 2025)
This study aims to evaluate the implementation of the Projek Penguatan Profil Pelajar Pancasila (P5) through cross-subject projects in building students’ character at MAN 3 Tanah Datar. The research employed a quantitative descriptive approach. The population comprised all teachers and students directly involved in P5 implementation. A total sampling technique was applied to teachers, while purposive sampling was used for students, resulting in 100 student respondents actively participating in P5 activities. Data were collected using a structured questionnaire with a five-point Likert scale to capture respondents’ perceptions of planning, implementation, evaluation, and outcomes of P5. Data analysis was conducted using descriptive statistical techniques. The findings indicate that P5 implementation at MAN 3 Tanah Datar has been generally well-executed across planning, implementation, and evaluation stages. P5 contributes positively to strengthening students’ independence, critical thinking, creativity, collaboration, and internalization of Pancasila values. However, variations in perceptions regarding the development of a positive school culture suggest the need for more consistent and sustainable implementation. Overall, the study highlights the potential of cross-subject P5 as an effective pedagogical approach for holistic character development and recommends strengthening stakeholder collaboration and continuity strategies for future practice.